Pelatihan Pelayanan Prima Bagi Anggota Asosiasi Homestay Manggarai Barat (Asihom Mabar) - Roseven Rudiyanto (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Currently, Labuan Bajo is a premium tourist destination. The status as a premium tourist destination has increased the tourism industry in Labuan Bajo. Tourism development in Labuan Bajo needs to be followed by the quality of tourism industry services, including accommodation services. One form of accommodation service is homestay. One of the obstacles homestays face is the inability to provide quality services to guests. Therefore, homestay managers in Labuan Bajo need excellent service training for homestay management. The implementation of this community service activity consists of three stages, namely preparation, implementation, and evaluation. At the implementation stage, the method used is lectures and discussions about service quality (SERVQUAL) and the five components of SERVQUAL. The pre-test and post-test methods were also used to measure the increase in understanding. There are six questions for the pre-test and post-test sessions. The pre-test results showed that the average level of correctness of the answers reached 89%, and the post-test results reached 93%. The correctness of the answers in the pre-test and post-test sessions showed that the participants experienced an increased understanding of quality services. Based on the results of the implementation of this excellent service training activity, it is recommended that homestay managers need training activities to improve their ability and understanding of homestay managers. In addition, training with the theme of optimizing social media as a digital promotion channel is also needed by homestay managers in Labuan Bajo.